The pigeon wants a puppy! - Willems, Mo. (New York [N.Y.] : Hyperion Books for Children, 2008)
The pigeon really, really wants a puppy, but when a puppy arrives the pigeon changes its mind.
A Junior Library Guild selection
Ages 2-6.
Keywords: Pigeons -- Juvenile fiction; Puppies -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Dogs -- Fiction; Picture books for children